ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PENYULUH PERTANIAN DAN HUBUNGANNYA DENGAN PRODUKTIVITAS PADI SAWAH RAWA LEBAK DI KABUPATEN BATANGHARI - Nababan, Halasson Sri Mai; Suandi, Suandi; Ningsih, Rozaina (Agros Journal of Agriculture Science, 2024)
This study aims to analyze the influence of age factors, number of training, length of service, number of assisted farmers, length of formal education and area of work on the performance of agricultural extension workers and the relationship between the performance of agricultural extension workers and the productivity of lowland rice fields in Batanghari Regency. The sampling method used a random sampling method with 40 PPL respondents and 101 farmer respondents. Data analysis used several analysis tools, namely Ordinal Regression analysis and Spearman Rank Correlation Analysis. The results showed that the factors that influenced the performance of PPL were the frequency of participating in training, length of service of extension workers, and the number of assisted farmers, while the age of the extension worker, length of education, and area of the assisted location did not significantly affect the performance of PPL, from the analysis of the relationship between the performance of agricultural extension workers and the productivity of lowland rice farming businesses did not have a significant relationship with a very weak relationship value.